Exploring the genetic intersection between obesity-associated genetic variants and insulin sensitivity indices - Suleman, Sufyan; Ängquist, Lars; Linneberg, Allan; Hansen, Torben; Grarup, Niels (Scientific reports, 2025)
Insulin sensitivity (IS) is a key determinant of metabolic health and may share genetic factors with obesity-related traits. Previous large-scale genetic studies have identified variants associated with IS as well as obesity related traits like body mass index (BMI) and waist-to-hip ratio (WHR). Notably, many of these associations are shared across traits, indicating a potential genetic overlap. However, the genetic intersection between IS and obesity-related traits remains underexplored. To explore this gap, we investigated associations between six IS indices, including fasting and post-glucose load measures, and genetic variants linked to BMI and WHR to determine their influence on IS and related cardiometabolic traits. To achieve this, we calculated six IS indices using fasting and oral glucose tolerance test (OGTT) data from 5,007 non-diabetic individuals, grouping them into fasting, OGTT 0,120 , and OGTT 0,30,120 categories. A total of 678 BMI-associated and 265 WHR-associated genetic variants were analysed using linear regression, adjusting for age and sex, with sex-specific analyses for WHR. Analyses were conducted with and without BMI adjustments and corrected for multiple testing (p adj ). Additionally, we explored the relationship between IS-linked variants and their associations with type 2 diabetes (T2D), coronary artery disease (CAD) and stroke. Among the 678 BMI-associated variants, 100 showed nominal associations ( p < 0.05) with at least one IS index; and 20 remained significant after multiple testing correction (p adj < 0.05) when not adjusting for BMI. After adjusting for BMI, 70 variants retained nominal associations, and six remained significant (p adj < 0.05). In sex-specific analyses of the 265 WHR-associated variants, 12 variants were associated in females when adjusted for BMI, whereas no significant associations were observed in males. Furthermore, BMI- and WHR-associated variants linked to decreased IS, such as those in FTO and VPS13C loci , were also associated with increased T2D and stroke risk, whereas IS-increasing variants, including those in VPS13C and PPARG , were linked to lower T2D and stroke risk, with some, like THADA , showing opposing effects on CAD. This study offers insights into genetic variants that influence both IS and obesity-related traits, revealing BMI- and WHR-associated variants with both positive and negative effects on IS and their potential impact on cardiometabolic health.